Effect of protein source and breed on embryo production in donor cows at a high-value genetic centre in Peru - León Trinidad, Silvia Eliana (2025)
Two sources of concentrated animal protein at 50 and 60% of the diet of high genetic value cows were evaluated on embryo production in donor cows. Twenty Braunvieh (BU), Brahman (BR), Simmental (SM), Gir (G) and Girolando (GIHO) cows were evaluated for seven months. The SM breed achieved a higher number of corpora lutea, similar to Brahman cows, but no difference was shown between the two protein rations. It was determined that using both protein sources decreases production costs per feeding, with the same results in embryo production. This study emphasizes the great importance of adequate protein nutrition in embryo transfer programs to maximize reproductive efficiency and embryo viability, taking into account the welfare of the animals subjected to these reproductive evaluations, in order to improve productivity in a center for the production and reproduction of material or germplasm of high genetic value.